TEACHING DIFFICULTIES IN THE INDONESIAN LANGUAGE TO EGYPTIAN STUDENTS WITH ARABIC AS AN INTERMEDIARY LANGUAGE - Amir Ramzy Botros Zakhary (Balai Bahasa Nusa Tenggara Barat, 2022)
The Indonesian Cultural Center in Cairo or “Pusat Kebudayaan Indonesia (Puskin) KBRI Kairo” offers a free Indonesian course consisting of 6 levels, each level taking almost three months. The teachers of the course are those who study at Al-Azhar University and speak the Arabic language well. Hundreds of Egyptian students join the course (level one), but only a few students finish up to the six levels. This study aims to identify problems and difficulties that are often encountered by Indonesian teachers in teaching the Indonesian language and the learning process in the classroom, from two points of view the Indonesian teachers and the Egyptian students. In addition, this study aims to know the reasons why many students don’t finish all levels of the courses and how to solve the problem. This descriptive qualitative study is subject to primary data, which are collected by questionnaires from Egyptian students and Indonesian teachers. The result of this study shows that the difficulties in teaching and learning the Indonesian language are categoriaed into linguistic difficulties, and non-linguistic difficulties.